Caracterización del estrés académico generado durante la pandemia del Covid-19 en estudiantes del programa de formación complementaria para Educadores de la Institución Educativa Normal Superior Juan Ladrilleros del Distrito de Buenaventura 2021 (2021)
The following research aimed to evaluate the characteristics of the academic stress generated during the covid-19 pandemic in a group of students from the complementary training program for educators at the Institution Escuela Normal Superior Juan Ladrilleros in the Buenaventura 2021 district. design is quantitative and descriptive. A sample of 25 people aged 17 to 37 years was taken from cycle three of the program. The SISCO inventory of the academic stress of Arturo Barraza was applied to them.